Versatile Wideband Polarization-Insensitive Mode Converter Based on Wedge-Shaped Waveguide - Yu Li; Minghua Chen; Hongchen Yu; Hongwei Chen; Sigang Yang; Shizhong Xie (IEEE Photonics Journal)
We propose and demonstrate a versatile, low-loss, polarization-insensitive, and wideband mode converter that can be utilized for mode conversion as a basic component in various photonic integrated circuits. The proposed converter is comprised of two reverse wedge-shaped waveguides and can be easily fabricated by a standard fabrication process. To verify its good performance and universality, we present two applications, including power coupling between a laser diode and a waveguide on the TriPleX platform and mode conversion between a strip waveguide and a slot waveguide on a silicon-on-insulator platform. For both examples, the insertion loss is less than −0.12 dB and −0.5 dB at around 1550 nm for the transverse electric (TE) mode and the transverse magnetic (TM) mode, respectively, by numerically study. Moreover, it maintains very low loss across a wavelength range of 300 nm for both polarization modes.